ANALISIS CUSTOMER EXPERIENCE DAN CUSTOMER TRUST TERHADAP KEPUTUSAN PASIEN BERKUNJUNG KEMBALI PADA KLINIK ALTERNATIF AKUPUNTUR SERUMPUN BAMBU - Arini, Diah Putri; Prabowo, Ari (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
This study aims to determine and analyze the influence of Customer Experience and Customer Trust on Patients' Decisions to Return to the Serumpun Bambu Alternative Acupuncture Clinic. This study uses an associative research design. The population in this study is all patients of the Serumpun Bambu Alternative Acupuncture Clinic, whose number cannot be determined with certainty. The sampling technique used is non-probability sampling with accidental sampling, using the Lemeshow formula. The number of samples taken in this study is 120 respondents. The questionnaire distribution focused on all patients of the Serumpun Bambu Alternative Acupuncture Clinic. The results of the study indicate that Customer Experience and Customer Trust partially have a significant influence on Patients' Decision to Return, while Customer Experience and Customer Trust together have a significant influence on Patients' Decision to Return. The determination coefficient of 72.1% indicates that the variables Customer Experience and Customer Trust can explain patients' decisions to revisit, while 27.9% is influenced by other factors outside the research model.